Answer:
3 ( x-1) (x+1) is the factored form
zeros are x=1, -1
Step-by-step explanation:
3x^2-3
Factor out a 3
3 ( x^2 -1)
What is inside the parentheses is the difference of squares
( a^2 -b^2) = ( a-b)(a+b)
3 ( x-1) (x+1)
To find the zeros, set this equal to zero
3 ( x-1) (x+1) =0
Using the zero product property
x-1 =0 x+1 =0
x=1, x=-1
Answer:
18
Step-by-step explanation:
21-n; n=3
Substitute n for 3:
Solve.
D.The answer should be about $10,000.The students answer is not correct.
You gave us the speed and the frequency, and you need the wavelength.
You were also nice enough to remind us that (fqy)x(lng) = speed.
So . . . F x W = 343 m/s
Divide each side by F :
W = (343 m/s) / F
W = (343 m/s) / (240 / s)
W = (343/240) m
<em>W = 1.429 meters</em>